3D Imaging of Skoteino Cave, Crete, Greece: Successes and Difficulties - Tyree, Loeta (2016)
Interpreting cave use, especially from antiquity, requires the perception of subterranean space in all dimensions (floor to ceiling to lateral extent) including spatial variability resulting from geological factors. Subterranean conditions, coupled with variable atmospheric conditions, create a special environment not readily conveyed by conventional mapping techniques limited to two-dimensional floor plans. Skoteino Cave in north central Crete, Greece was used as a ritual and refuge site in the Bronze Age and later. Mapping of the cave attempted to depict and interpret prehistoric and historical use of this space by employing two mapping techniques: EDM total station mapping and terrestrial/point cloud laser scanning. Comparisons with earlier methods used to map cave show the advantages and disadvantages of various mapping schemes. To date, this was the first use of three-dimensional (3D) scanning to explore the complex shapes and space of a subterranean archaeological site on Crete (and the second such use in Greece), and this use demonstrates its own consequent successes and difficulties.